Exploring treatment needs among women who prostitute. Issue 3 (3rd July 2021) - Murnan, Aaron
ABSTRACT: Women engaged in street-level prostitution (SLP) report high treatment recidivism rates and worse substance use treatment outcomes compared to other treatment-seeking women. Even so, few efforts have been made to understand or address the treatment needs of this population. This qualitative study recruited 15 women with histories of SLP, who have sought substance use treatment previously to directly explore their prior treatment experiences, barriers, and desires. An Inductive Content Analysis was utilized to interpret qualitative data and identify emergent themes within respondent's accounts. Participants experienced significant barriers to substance use treatment including judgment, stigma and limitations of treatment at supporting their salient treatment desires. Social connection that can be facilitated through substance use treatment appeared to be uniquely valuable, possibly related to social isolation commonly reported among this population. Current findings offer initial guidance toward future research questions and intervention development efforts.